The Effect of Money Supply and Interest Rates on Inflation in Indonesia - Pisganidy, Marla; Awaluddin, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2025)
The determinant of a country with a stable economy is measured by the inflation rate which is the main factor in economic development, Inflation is a situation where price increases occur continuously in one period. The purpose of this study is to see the influence of Money Supply and Interest Rates in Indonesia. This research method uses ECM (Error Correction Model) and the data used is data from the period 2005 – 2020. The results of this study show that the Money Supply has a significant effect on Inflation. For interest rates, it shows results that have a significant effect on inflation. Based on the results of the study, in the long term the variable amount of money supply (X1) has no effect on the variable inflation (Y) in Indonesia, while in the short term the amount of money supply has an effect on inflation in Indonesia. For the Variable Interest Rate (X2) both in the long and short term it affects the inflation variable (Y) in Indonesia